Prospective Teachers’ Reflection Toward the Implementation of Independent Curriculum in Teaching Practice Program - Mardiana, Wiwik; Krisdiana, Amy; Afkar, Taswirul; Anjariyah, Deka (IJECA (International Journal of Education and Curriculum Application), 2023)
Reflection has a vital contribution to improving teachers’ teaching performance as well as their professional growth. Therefore, this research investigates how prospective teachers apply reflection activities in teaching and learning and the impacts of the implementation of an independent curriculum during teaching practice program activities. Using qualitative research, the researchers employed a group interview consisting of two participants in each group. The participants were six prospective teachers who accomplished the teaching practice program. Three types of reflections were employed, i.e., reflection-before-lesson, reflection-during-lesson, and reflection-after-lesson. The results indicate that teachers’ reflective practice leads to improvement in their teaching process and builds engagement with the students. The insights of the research results are further discussed.